Magnesium intake and serum magnesium concentration in children with type 1 diabetes mellitus: association with glycemic control and clinical symptoms - Dobrovolska, Lesya; Boyarchuk, Oksana (Frontiers in Nutrition, 2024)
IntroductionMagnesium is involved in numerous reactions that regulate the functioning of different organs and systems. Hypomagnesemia impacts on the development of various metabolic disorders, including insulin resistance and diabetes mellitus (DM). Studying magnesium levels in children with type 1 DM is crucial, as deficiencies are linked to many diabetes complications. The study aimed to determine dietary magnesium intake, serum magnesium concentration in children with type 1 DM, and their impact on the clinical course of DM.MethodsThis case-control study involved 50 children with type 1 DM (cases) and 67 healthy children (control) aged 6–17 years. We conducted a survey to gather basic characteristics, weekly consumption of specific food items, and clinical data for patients with DM and healthy children. Additionally, serum magnesium, calcium, and phosphorus concentration were measured.ResultsInsufficient magnesium dietary intake was observed in 46% of patients with DM and in 34.3% of healthy children (p > 0.05). Serum magnesium concentration in healthy children was higher than in children with DM (0.94 ± 0.24 vs. 0.84 ± 0.14, p = 0.011), although the proportion of children with hypomagnesemia did not differ between the groups (11.9% and 14.0%, respectively). Hypomagnesemia was more frequently observed in children from rural areas in both groups: 85.7% in children with DM (p = 0.054) and 62.5% in healthy children (p = 0.010). All children with hypomagnesemia had poor DM control compared to 61.3% of patients with normal magnesium concentration (p = 0.047). The mean magnesium concentration in children with optimal glycemic control was significantly higher than in children with poor control (0.96 ± 0.09 vs. 0.78 ± 0.14 mmol/L, p = 0.001). In DM children and hypomagnesemia, significant decreases in serum calcium and phosphorus concentrations were observed (p = 0.008 and p = 0.017, respectively). Headache and attention disorders were significantly more frequent in DM patients with hypomagnesemia (71.4% vs. 20.9%, p = 0.006; 28.6% vs. 4.7%, p = 0.031, respectively).ConclusionThe study demonstrates lower serum magnesium levels in children with type 1 DM than in healthy children, with a higher prevalence of hypomagnesemia in rural areas and those with poor glycemic control. Hypomagnesemia in DM children was associated with lower serum calcium and phosphorus levels, as well as more frequent symptoms such as headaches and attention deficits. Monitoring of serum magnesium is essential in routine care of children with DM.